Muslim Andalusia: new insights into linguistic and literary exchanges between the East and the West - Bahjat, Munjid Mustafa; Ramdane, Tahraoui; Preece, Abdul Shakour Duncan (IIUM Press, International Islamic University Malaysia, 2018)
This paper offers a new perspective on the cultural relations between Arab Muslims of the East and Christians of the West, in medieval Iberia (known as al-Andalus by the Muslims) from 711 to 1031 C.E, identifying the benefits that emerged from such relations. Evidence has been extracted from primary historical sources, including the travel writings of Ibn Hayyan and Ibn Jubayr, along with other Western sources and writings born out of the academic exchange of ideas and literature between Muslim Spain and the European states of the time. The discussion also draws upon manuscripts and studies that transcend the stereotypical images of the victors and the defeated. The main thesis of this study argues that universal values and mutual respect between Muslim and non-Muslim communities of medieval Spain were in fact the norm and not the exception. It endeavours to show that literature, in all its forms, had a significant impact on the development and maintenance of harmonious, peaceful relations between Muslims and non-Muslims (mainly Christians). The paper highlights the synthesis between the Arabic and Spanish languages, between Arabic and European poetry and between Arab and European tales and stories. The findings contest the idea of a clash of civilisations and instead demonstrate how in medieval Spain, people of various creeds and cultures communicated and interacted successfully in spite of their religious and cultural differences.